In vitro expression analysis of the ITGB3 c.598G/A mutation and its association with FNAIT - DING Haoqiang; YE Xin; XU Xiuzhang; XIA Wenjie; DENG Jing; LIU Jing; CHEN Yangkai; CHEN Dawei; XU Yaori (Zhongguo shuxue zazhi)
[Objective] To explore the role of the c.598G>A mutation of the ITGB3 gene in the occurrence of fetal and neonatal alloimmune thrombocytopenia (FNAIT) through its expression in vitro. [Methods] The platelet antibodies in the sera of the affected neonate and her mother were detected using commercial enzyme-linked immunosorbent assay (ELISA), solid-phase agglutination, flow cytometry and the gold standard monoclonal antibody-specific immobilization of platelet antigens (MAIPA). The common human platelet antigen (HPA) genotypes of the neonate and her parents were obtained using the HPA-SSP method. The presence of mutations was analyzed by sequencing the exons of the ITGB3 and ITGA2B genes. The target gene of ITGB3 was obtained by PCR amplification using the existing human platelet cDNA. The wild-type ITGB3 eukaryotic expression vector was constructed by TA cloning technology. The 598G>A mutant ITGB3 eukaryotic expression vector was obtained by point mutation, and the plasmid DNA was co-transfected with that of ITGA2B (αⅡb) into HEK293 cells. The transfected cells stably expressing GP Ⅱb/Ⅲa were screened and obtained. The expression of GP Ⅱb/Ⅲa in 598G>A mutant transfected cells and the presence of antibodies against this mutation in the serum of mother were detected by flow cytometry and MAIPA. [Results] Antibodies against HLA-class Ⅰ and GP Ⅱb/Ⅲa glycoproteins were detected in the serum of the neonate's mother, and subsequent HLA antibody-specific testing confirmed the presence of antibodies against HLA-B* 57∶01 and A* 02∶05. ITGB3 sequencing showed that the neonate and her father carried the c.598G>A point mutation, which results in the change of glutamate to lysine at position 200. Antibodies against GP Ⅱb/Ⅲa glycoproteins were not detected using constructed c.598G>A mutant transfected cells reacted with the maternal serum. [Conclusion] The in vitro expression and analysis of the ITGB3 c.598G>A mutation did not support a role for this mutation in the pathogenesis of FNAIT. The establishment of this method facilitates the discovery of new platelet low-frequency antigens, and provides a theoretical foundation for the detection of antibodies against platelet antigens associated with patients with adverse pregnancy and childbirth histories.